A militância conservacionista de Augusto Ruschi: práticas científicas e estratégias políticas na construção da biologia e da conservação da natureza no Brasil (1937-1986) - Gonçalves, Alyne dos Santos (2018)
In this study, the focus is on the aspects of the work of the scientist Augusto Ruschi (1915-1986) regarding the knowledge of the natural world and the social political strategies for its preservation. Since he joined the charts of the National Museum of Rio de Janeiro in 1939 and the foundation of the Prof. Mello Leitão Biology Museum, in 1949, in Espírito Santo, Ruschi has worked in political scientific nets built within the intersection of professional calculation, political interests and socio-economical demands that enabled researches and public interventions which have contributed for the process of institutionalization of the Biological Science in Brazil especially regarding nature preservation. Based on the critics to the standard conception of “Science”, made by the so-called “social studies of Science”, I analyze scientific reports and mail exchanged between Ruschi and different people in order to understand a scientific production, locally contextualized, which tried to integrate the collection of natural history with experimental practices in laboratories, as well as linking so heterogeneous social actors such as loggers and Indians, conservationists and businesspeople, journalists, Generals, etc. I explore two different theoreticalmethodological approaches: Pierre Bourdieu, to understand the structure of the scientific field of Biology and the conservationism in Brazil; and Bruno Latour, to analyze scientific controversies within the process of building contents and research methods related to that field, such as the issue of reforestation and the valorization of the Indian knowledge. I argue that the discipline Nature Preservation, as thought and performed by Ruschi, is characterized by a broad view of the Science, involving experimentation, observation, collection and categorization of the flora and fauna, but also Sociology, History and Politics, the scientific practice conceived as instrument to assure the protection of a minimum of nature, for the benefit of the present and future generations. I conclude that Augusto Ruschi has taken Science as a social practice connected to the demands of his time, a knowhow represented by the connection with other knowledge over the tendency to the partition of life.